Konflik Batin Tokoh Utama Dalam Novel Adaptasi Penyalin Cahaya Karya Lucia Priandarini: Kajian Psikologi Sastra - Alifia Ulfadila; Siti Fatimah; Muhajir Muhajir (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The novel entitled Penyalin Cahaya by Lucia Priandarini is interesting to examine from the aspect of the inner conflict experienced by the main character. The inner conflict that occurs in the novel is caused by a case of sexual harassment against the main character. The aim of this research is to describe the inner conflict experienced by the main character of the novel Pelipin Cahaya by Lucia Priandarini. The method used in this research is descriptive qualitative. The approach used is a literary psychology approach. The data collection technique used is a documentation technique in three ways, namely, literature study, reading technique, and note-taking technique. The instrument used is a data card for classifying forms of inner conflict. The analysis technique used is descriptive analysis technique. The results of this research found 50 data on forms of inner conflict and 50 data on causes of inner conflict. The forms of inner conflict found were (3) depression, (2) obsession, (7) anxiety, (4) frustration, (2) feeling of security, (3) dissatisfaction, (7) hurt, (6) fear, (4) guilt, (8) anger, and (4) inadequacy. Meanwhile, the causes of inner conflict found were (5) physiological needs, (22) security needs, (7) love and belonging needs, (7) self-esteem needs, and (9) self-actualization needs. This research can have implications for literature learning at the high school/vocational school level.